1995
DOI: 10.1111/j.1432-1033.1995.0465k.x
|View full text |Cite
|
Sign up to set email alerts
|

Structural and Functional Importance of the C-Terminal Part of the Pulmonary Surfactant Polypeptide SP-C

Abstract: A synthetic non-palmitoylated form of the pulmonary surfactant protein SP-C and three peptides of different lengths corresponding to its N-terminal and middle parts were reconstituted into dipalmitoylglycerophosphocholine/phosphatidylglycerol (7:3, by mass) lipid bilayers. The adsorption properties of each reconstituted system were determined by measurement of the surface pressure after injection of the samples underneath an air/water interface. Attenuated total reflection infrared spectroscopy provided inform… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
16
1

Year Published

1996
1996
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 16 publications
(19 citation statements)
references
References 53 publications
2
16
1
Order By: Relevance
“…This indicates that it is more important to capture the extreme hydrophobicity and highly helical structure of SP-C rather than its exact side chain chemistry, which is consistent with previous studies of peptide analogues 53 .…”
Section: Synthetic Sp-c Analoguessupporting
confidence: 89%
“…This indicates that it is more important to capture the extreme hydrophobicity and highly helical structure of SP-C rather than its exact side chain chemistry, which is consistent with previous studies of peptide analogues 53 .…”
Section: Synthetic Sp-c Analoguessupporting
confidence: 89%
“…Such interactions are difficult to envision with the KL4 helical surface and orientation in a phospholipid bilayer now found, suggesting another mechanism of action for KL4 in pulmonary phospholipids. The secondary structure and transmembranous orientation of KL4 prompts investigation of its spreading properties in a lipid mixture, since another transmembrane helix (SP-C/BR) with a primary structure which is unrelated to any of the pulmonary surfactant proteins has significant effects on lipid spreading kinetics [20,26]. KL4 does accelerate the spreading of lipids at an air/water interface but it is less effective than both native SP-C and the SP-C/BR hybrid in this respect.…”
Section: Orientation Of Kla In a Phospholipid Bilayermentioning
confidence: 99%
“…interface Spreading kinetics of 2% (w/w) of KL4 in a DPPC/PG/PA 68:22:9 (by weight) mixture at an air/water interface was compared to that of native SP-C and SP-C/BR [20], both with transmembranous c~-helices in similar phospholipid mixtures [11,12,14,26]. KL4 is less efficient than native SP-C and SP-C/BR in accelerating the spreading of the lipid mixture and also reaches a lower surface pressure after 1 min (Fig.…”
Section: Effects Of Kl4 On the Spreading Of Lipids At An Air~watermentioning
confidence: 99%
“…Human SP-C FGIPCCPVHLKRLLIVVVVVVLIVVVIVGALLMGL the N-terminal region supported that the a-helical structure determined in organic solvents exists in lipid detergents and phospholipid bilayers, making it most likely that it represents the structure of SP-C in native surfactant [110][111][112][113]. Importantly, the length of the entire SP-C a-helix determined in organic solvents (37 A), and of its central part that contains exclusively non-polar residues (23 A), perfectly matches the thickness of a fluid DPPC bilayer and its central part composed of non-polar fatty acyl chains respectively [111].…”
Section: Polypeptide Sequencementioning
confidence: 91%
“…In agreement with the strong preference for b-sheet structure of a polyVal sequence, synthetic replicas of SP-C form mainly b-sheet aggregates, which, when combined with synthetic phospholipids, show low surface activity in vitro [193]. A first indication how this obstacle could be circumvented came from the observation that replacing the polyVal transmembrane segment with the amino acid sequence of the second transmembrane helix of bacteriorhodopsin, which lacks sequence resemblance to SP-C, resulted in a hybrid peptide (SP-C/ BR, Table 2) with high a-helical content and good surface activity in vitro [110,193]. This suggested that the a-helical conformation of the transmembrane region as such, rather than the amino acid sequence, is of prime importance for the biological function of synthetic SP-C analogues [193].…”
Section: Development Of Sp-c Analoguesmentioning
confidence: 99%